Acute Pancreatitis Associated With Antipsychotic Medication: Evaluation of Clinical Features, Treatment, and Polypharmacy in a Series of Cases. Issue 2 (April 2016) - Silva, Matthew A.; Key, Sujin; Han, Edward; Malloy, Michael J.
Abstract : Background: Antipsychotic-associated acute pancreatitis presents like pancreatitis from other causes, requiring clinical judgment, tests, and decision support to establish the diagnosis. Many new cases of atypical antipsychotic pancreatitis have been established, and current decision supports are out of date as antipsychotic polypharmacy is being recognized. Given the population frequency of psychosis and frequency of antipsychotic prescribing, we reviewed published cases summarizing common clinical findings and antipsychotics associated with acute pancreatitis to updating earlier decision support. Methods: Case reports of antipsychotic pancreatitis from 1990 to 2015 were reviewed and abstracted by independent reviewers. Demographic, clinical features, management, and Naranjo and probability scores were abstracted and reviewed for associations. Appropriate statistical tests were selected for normally and non–normally distributed data. Results: We summarized 41 cases of acute pancreatitis associated with antipsychotics, and cases were younger men (59%) (mean age, 39 years). Alcohol, diabetes, and previous lithiasis appeared in 27%; polypharmacy was associated with 53% of cases, and 80% had concomitant use of other medication linked to pancreatitis. The median lipase, amylase, and alkaline phosphate during acute presentation were 1210 IU/L (range, 243–5482 IU/L), 492 IU/L (range, 3–2916 IU/L), and 152 IU/L (range, 119–367 IU/L), respectively. Median exposure to antipsychotics were 49 days (range, 5–3, 650 days); most were mild (63%, n = 26), several severe (27%, n = 11), and few fatal (10%, n = 4). Discussion: We identified 41 reports of antipsychotic-related acute pancreatitis, many associated with antipsychotic polypharmacy. Olanzapine, risperidone, quetiapine, aripiprazole, and ziprasidone are associated with acute pancreatitis and often in combination with mood stabilizers.